Cannabigerol and cannabichromene in Cannabis sativa L. - Zagožen Marjeta; Čerenak Andreja; Kreft Samo (Acta Pharmaceutica)
In addition to delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD), other phytocannabinoids, such as cannabigerol (CBG) and cannabichromene (CBC), also have beneficial effects on human health. A high content of CBG is found in plants with the B0 genotype, whereas CBC is independent of the allelic chemotype locus B. In basic research models such as mice or rats, CBG has demonstrated anticancer properties, particularly against breast cancer. CBG has shown anti-inflammatory effects on murine colitis and on inflammatory bowel disease as well as stimulatory effects on the feeding behaviors of mice. It has also exhibited inhibition of aldose reductase, which is known to cause an accumulation of sorbitol and increase glucose levels in the blood, which may lead to diabetes. Cannabinoid CBC has also shown anti-inflammatory effects and reduced hypermobility in the gut and has displayed potential in vitro effect on adult neural stem progenitor cells. CBC also exerts modest analgesic properties in rodents, as well as anti-fungal, anti-bacterial, pro-apoptotic, and anti-proliferative effects in tumor cells.